The Effect of Management Contract Implementation on Public Hospitals' Performance: A Case Study in Iran - Omid Barati; Ahmad Sadeghi; Mohammad Amin Bahrami (Shahid Sadoughi University of Medical Sciences, 2019)
Background: This study aimed to investigate the effects of using a management contract mechanism on hospital's performance indicators. Methods: A longitudinal comparative study was done in 4 educational hospitals affiliated to Iran University of Medical Sciences, Tehran, Iran. The related data to 17 performance indicators (including 4 financial, 6 facility utilization, 2 customers, 3 human resources, and 2 quality indicators) of the studied hospitals were collected for two years before management contract implementation and two years after its implementation using hospital information system (HIS). The collected data were ordered and analyzed using EXCELL and SPSS18 software. Results: The results showed the positive effects of contract management implementation on some financial, facility, customer, human resources and quality indicators. Hospital income, patients' satisfaction, staff satisfaction and the number of inpatients and outpatients of studied hospitals improved significantly after contracting. Conclusion: Although, the present study showed the benefits of contracting process in delivering hospital services, its success largely depends on the clear monitoring of contract and the continuous development of the managerial capacity of contractors.